Birmingham revolution : Martin Luther King Jr.'s epic challenge to the church - Gilbreath, Edward, 1969- (Downers Grove, Illinois : IVP, An imprint of InterVarsity Press, 2013)
As with almost no other movement before or since, Christian people gave force to a social mission. And, remarkably, they did it largely through nonviolent actions. Dr. Martin Luther King Jr.'s words and historic efforts as the Moses of this civil rights movement stand out as perhaps the most significant instance of a modern Christian leader acting in a prophetic role to instigate political change. In many ways "The Letter from Birmingham Jail" stands at the center of that movement. In this book African American journalist Edward Gilbreath explores the place of that letter in the life and work of Dr. King. Birmingham Revolution is not simply a work of historical reflection. Gilbreath encourages us to reflect on the relevance of King's work for the church and culture of our day.
Prologue: King's Wittenberg moment -- Birmingham begins -- The making of Martin -- Montgomery miracle -- The road to revolution -- As Birmingham goes -- Eight white preachers, or with friends like these -- An angry Dr. King -- The jailhouse manifesto -- "My dear fellow clergymen" -- Taking it to the streets -- Dreams and nightmares -- After the revolution -- King among the evangelicals -- Epilogue: King's Epistle for today.
Includes bibliographical references (pages 175-197) and index.
Keywords: Christian life -- United States; United States -- Church history -- 20th century; Christianity and culture -- United States; King, Martin Luther, -- Jr., -- 1929-1968.; Reconciliation -- Religious aspects -- Christianity; Race relations -- Religious aspects -- Christianity; Civil rights -- Religious aspects -- Christianity